The Making of Canadian Economists - Results of a Survey of Graduate Students - Grubel, Herbert G. (Canadian Journal of Higher Education, 1991)
The responses to questions by 155 students revealed the following, most important facts. The students predominantly came from families with high incomes. They have leftist political leanings, though through their training, more have turned right than left. The students share most strongly the views on fundamental propositions in economics held by U.S. graduate students and less those held by Canadian and U.S. professionals. Students from different Canadian universities hold very similar views on price-theoretic propositions but rather widely differing views on some important issues of macro-economics and income distribution. The most important finding is that, like their U.S. colleagues, Canadian graduate students believe that for professional success it is more important to learn technical skills rather than about institutions, history and policy. As a result they end up poorly prepared for work on economic policy issues and their research tends to lack real world relevance, even though real world and policy problems attracted them to the graduate programs.